Examining optoelectronics in machine vision and applications in industry 4.0 - Sergiyenko, Oleg 1969-; Rodrâiguez-Quiänonez, Julio C. 1985-; Flores-Fuentes, Wendy 1978- (IGI Global, 2021)
"This book focuses on the examination of emerging technologies for the design, fabrication and implementation of optoelectronic sensors, devices and systems using a machine vision approach to support industrial, commercial and scientific applications"--